Renal Disposition of Colistin in the Isolated Perfused Rat Kidney - Ma, Zheng (American Society for Microbiology (ASM), 2009)
Nephrotoxicity is an important limitation to the clinical use of colistin against Pseudomonas aeruginosa and other gram-negative pathogens. Previous work reported net tubular reabsorption of colistin by the kidney in vivo, but there is no knowledge of its disposition within the kidney. This study investigated the renal disposition and potential transport mechanisms of colistin in the isolated perfused rat kidney (IPK) model by perfusing with colistin sulfate alone (2 μg/ml) or in the presence of potential inhibitors (tetraethylammonium [TEA], glycine-glycine [Gly-Gly], or hydrochloric acid [HCl]) at three different concentrations. When perfused alone, the renal clearances (CL(R)) for colistin A and B (the major components of colistin) in control kidneys were constant and low (mean values < 0.05 ml/min throughout the perfusion). The mean clearance ratios [CR, defined as CL(R)/(f(u) × GFR), where f(u) is the fraction of drug unbound in perfusate and GFR is the glomerular filtration rate] were significantly less than 1. It was concluded that there is net tubular reabsorption of colistin, and this exceeded the reabsorption of water. Less than 10% eliminated from perfusate was recovered in urine, suggesting considerable renal accumulation of colistin. The CR values for colistin were significantly increased when perfused with TEA (500 μM), Gly-Gly (833 μM), and HCl (2,500, 5,000, and 10,000 μM). It is proposed that renal reabsorption of colistin may involve organic cation transporters (inhibited by TEA) and peptide transporters (inhibited by Gly-Gly) and that the process is sensitive to the pH of urine.